Preparation and evaluation of in-situ gels containing hydrocortisone for the treatment of aphthous ulcer - Sanjana A; Mohammed Gulzar Ahmed; Jaswanth Gowda BH (Elsevier, 2021)
Aphthous ulcers are painful sores that may occur in the mouth's mucous membrane and are the most common type of oral lesions. The present research is aimed to develop in-situ gel of hydrocortisone for the treatment of aphthous ulcers. Temperature induced in-situ gels were prepared by using various concentrations of methylcellulose. The prepared formulations were evaluated for the conversion of sol-gel transition temperature or gelation temperature, gelling capacity, pH, viscosity, syringeability, spreadability, drug content, In vitro and ex vivo studies. The gelation temperatures of the prepared formulations were found to be in the range of 32-39 ​°C. The formulations exhibited fairly uniform drug content (76.40-94.7%) and pH was found to be 6.8. In vitro drug release was carried out for 8 ​h using phosphate buffer as a diffusion medium. In-situ gel formulation containing 1% w/v of methylcellulose as a gel base prolonged the drug release up to 8 ​h and showed sustained release behaviour. Via these, in-situ gel formulations, the release kinetics of the drug was first order. Finally, it can be inferred that in-situ gel formulation containing 1% w/v of methylcellulose facilitates prolonged drug release, extended drug residence period, which in turn improves the bioavailability of drugs. The short-term stability studies were carried out and no substantial changes were observed.